Siri’ Na Pacce dan Regulasi Diri Pelajar Buddhis Kota Makassar - Ahsanul Khair Asdar (STABN Sriwjaya, 2020)
This research was an ethnographic study with a qualitative approach. It aims to describe siri 'na pacce as a cultural philosophy of the Buginese and Makassarnese to self-regulation of Buddhist students in Makassar. This study involved Buddhist students at the junior and senior high schools in Makassar. The subjects were selected using purposive and snowball throwing methods. The research data were collected by interview, questionnaire distribution, and documentation study. The research data were analyzed with Miles, Huberman, and Saldana interactive analysis model (data collection, data condensation, data display, and conclusions drawing/verification). The results showed that siri' na pacce as a cultural philosophy of the Buginese and Makassarnese had a strong relation to the self-regulation of Buddhist students in Makassar. They had good self-regulation when they had a sufficient understanding of siri' na pacce. It can be seen in the form of (1) avoiding cheating on assignments and answers when carrying out exams and not giving answers when carrying out exams, (2) always maintaining good grades in the learning process, including when doing assignments or taking exams, (3) working hard to get brilliant achievements in school, (4) respecting and respecting teachers and classmates, especially during discussion sessions, greeting teachers politely in the school environment, and obeying the rules set by the school, (5) doing learning activities together without discriminating or being picky and prioritizing togetherness in learning activities, and (6) helping friends who have not mastered the learning material to their abilities, helping friends who experience disaster even though they aren't Buddhist, and learn to put yourself in the shoes of others who are having difficulties or calamity.